The Effectiveness of Spiritual Psychotherapy on Patients with Mental Disorders: A Systematic Review - Ahmad Wahyudi; Ah Yusuf; Mundakir (Poltekita : Jurnal Ilmu Kesehatan, 2021)
Recently, the research analyzes the relationship between religion and spirituality has grown rapidly.Many mental health clinics have implemented interventions on religious and spirituality-based mental disorders. This article aimed to examine the effectiveness of handling mental-based mental disorders from various studies that have been conducted. Methods: The articles used in this systematic review were searched in the SCOPUS, PROQUEST, SPRINGERLINK, SAGE and SCIENCEDIRECT databases which is published between 2016-2020. The keyword used were "mental disorders" or "mental illness" and â€œspiritualâ€ or â€œreligiousâ€, with the use of the phrase Boolean Operators. The articles selected according to the inclusion criteria include articles stating the effectiveness of spiritual healing for mental disorders, articles that analyzed mental illness patients in RCT, case-control studies and experiment. The articles obtained then were analyzed with the DSVIA conclusion table (design, sampling, variables, intervention and analysis). Results: There were 15 articles that meet the criteria as a systematic review.Thestudy result showed that there was a relationship between religious/spiritual involvement and mental disorders (positive). The findings from previous research indicated that religion play an important role in many situations because religious beliefs and rules affect people's lives. Conclusions:The majority of the previous literature stated a significant relationship between religious beliefs and practices and mental health.